A influência dos Smartphones na relação ensino/aprendizagem em uma escola de ensino médio da zona rural da região metropolitana de São Luís/Ma - PORTELA , Christian Albert da Silva (2019)
The development of digital technologies has brought a significant set of changes to the teaching and learning process, from mobile communication and information devices to new methodologies and conceptual models of teaching. The purpose of this study was to analyze the influence of smart-phones in a rural school, their use in pedagogical activities, transformations in teaching-learning relationships, and the consequences on teaching-learning relations in the exchange of information and knowledge. The school was located in the municipality of Paço do Lumiar, an area in transition from rural to urban as it is absorbed by metropolitan region of São Luís / MA, Brazil. The qualitative/quantitative approach is used in field research in the perspective of “Dialectical Historical Materialism” and the instruments used were: observations recorded in field notes, questionnaires completed by seventy-one students, and interviews with four teachers. The results show that the use of the smart-phone in the classroom can constitute a transforming material element of the pedagogical praxis, and that the teachers who have started to introduce it into their classroom practices have been successful, despite what we classify as "functional deviation in the digital immersion" (DFID), a phenomenon widely observed by teachers which gives rise to concern on their part, as the device has a subjective rather than objective functionality, being multifunctional, or dysfunctional (as Baudrillard tells us about technological objects: gadgets). Another result observed was the need for greater attention from the educational authorities in Maranhão to the quality of the connectivity infrastructure offered by the school unit, which in this case is precarious, and we can infer that other rural school units more distant from large urban centers suffer from the same precariousness. This is incompatible with the educational and pedagogical needs of the 21st century, relegating the school community to a process of "digital exclusion", which in this case is promoted by the educational institution. We also note the need for a curriculum that is formative and teaching that is more adapted to the times of ubiquitous connectivity, as is the case of the “web curriculum”, a curricular proposal more appropriate to our times. References for this research include among others - for the question of technological objects and cyberculture: Pierre Lévy (1993/1995/1999) and Jean Baudrillard (1992/1995/2009); for the methodology of Dialectical Historical Materialism: Karl Marx (2008), Karel Kosik (2002), Frigotto (2000), Vazquez (2003); instruments: Triviños (1987) and Manzini (2003); State of knowledge: Ferreira (2002) and Romanowski (2006); Knowledge of Teaching: Tardif (2000) and Masetto (2000).